THE INFLUENCE OF PRICE AND PRODUCT INNOVATION ON PURCHASING DECISIONS AT FROZEN FOODKU BATAM CITY - Budi Garjito; Eko Triono; Hendri Herman (PENANOMICS: International Journal of Economics, 2022)
The purpose of this study was to determine the Effect of Price and Product Innovation on Purchasing Decisions at Frozen Foodku Batam City. The formulation of the problem in the study is Does Price have a significant effect on purchasing decisions at Frozen Foodku Batam City?, Does product innovation have a significant effect on purchasing decisions at Frozen Foodku Batam City?, Does price and product innovation affect simultaneously on purchasing decisions at Frozen Foodku Batam City. This research uses a quantitative research approach. This type of research includes causal associative research. The population in this study was 2.489 consumers. The sampling technique used in this study was an axidental sampling technique with 96 respondents as research samples. The analysis used in this study is a simple linear regression analysis and multiple liner regression analysis. The results of the t test analysis showed a significant level of X1 was at the level of 0.000 (0.000<0.05) with a calculated t value of 2.505 while X2 was at the level of 0.000 (0.000>0.05) with a calculated t value of 13,114, and based on the F test the variables X 1 and X 2 were both at the level of 0.00 (0.000 <0.05). Based on the results of the study, it can be concluded that price has a significant effect on purchasing decisions and product innovation has a significant effect on purchasing decisions. And based on the F test, it is proven that price and product innovation have a significant effect on purchasing decisions. .